Encyclopedia of Judaism - Karesh, Sara E. (Encyclopedia of world religions., 2006)
Encyclopedia of Judaism explores a tradition that has a 2,000-year recorded history and has been a part of the culture of almost every country and society around the globe. Encapsulating all things Jewish--language, laws, literature, arts, theology, ritual, land, culture, and personalities--this authoritative volume offers readers ba access to Judaism from both a historical and contemporary perspective.